2021
DOI: 10.1007/s10854-021-06660-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of Cu-doped TiO2 nanomaterials with anatase/rutile/brookite triphasic structure and their photocatalytic activity

Abstract: Pure TiO 2 and different concentrations of Cu-doped TiO 2 with anatase/rutile/brookite triphasic structure were successfully synthesized through a simple hydrothermal process and characterized by X-ray diffraction (XRD), Raman, scanning electron microscope (SEM), transmission electron microscope (TEM), X-ray photoelectron spectra (XPS), diffuse re ectance spectra (DRS), photoluminescence spectra (PL) and Brunauer-Emmett-Teller surface area (BET). Both pure and Cu-doped TiO 2 show relatively high photocatalytic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 52 publications
0
22
0
Order By: Relevance
“…The high-resolution spectra of O 1s are shown in Figure 4 c. The O 1s of PT was decomposed into two peaks corresponding to the lattice oxygen (O L ) and surface hydroxyl (O H ), located at 529.9 eV and 531.2 eV, respectively. The peaks of the lattice oxygen and surface hydroxyl of LST sample were at 530.0 eV and 531.1 eV respectively [ 30 ]. It can be observed that the surface hydroxyl peak area of the LST sample was significantly larger than that of PT, indicating that the co-doping advanced the surface adsorption performance and introduced more OH − groups on the particle surface.…”
Section: Resultsmentioning
confidence: 99%
“…The high-resolution spectra of O 1s are shown in Figure 4 c. The O 1s of PT was decomposed into two peaks corresponding to the lattice oxygen (O L ) and surface hydroxyl (O H ), located at 529.9 eV and 531.2 eV, respectively. The peaks of the lattice oxygen and surface hydroxyl of LST sample were at 530.0 eV and 531.1 eV respectively [ 30 ]. It can be observed that the surface hydroxyl peak area of the LST sample was significantly larger than that of PT, indicating that the co-doping advanced the surface adsorption performance and introduced more OH − groups on the particle surface.…”
Section: Resultsmentioning
confidence: 99%
“…The active species of CT650-R25 and CT650-R0 during the photodegradation process were studied. Ammonium oxalate (AO), 1,4-benzoquinone (BQ) and tert-butanol (TBA) [ 1 ] were added to capture superoxide radical species ·O 2 − , h + and hydroxyl radicals (·OH), respectively. The different degradation results of CT650-R25 are exhibited in Figure 6 a.…”
Section: Resultsmentioning
confidence: 99%
“…With the continuous growth in population and rapid development of the economy, the problem of environmental pollution has increased. Organic dyes such as methyl orange (MO), methylene blue and rhodamine [ 1 ], and antibiotics such as tetracycline (TC) [ 2 , 3 ], have become major pollutants affecting the water environment. Untreated organic dyes are often slowly naturally degraded.…”
Section: Introductionmentioning
confidence: 99%
“…This decrease in band-gap energy shifts wavelengths from the ultraviolet to the visible region. Cu loading increases with the changes in band-gap energy and wavelength and TiO2-conjugated Cu shows more stability with higher photo-catalytic activity in visible light (λ > 400 nm) [8]. This process involves no expense as it occurs at room temperature under atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%